The cafe at beach end - Thayne, RaeAnne (Canary Street Press, 2023)
One of the most hated women in the country, Meredith Collins, whose late ex-husband was guilty of embezzlement and fraud, returns to the beach town of Cape Sanctuary to help run her late grandmother's Last Hope Café with her cousin, and meets and falls in love with a man who is not what he seems.